(untitled) (TAMADDUN NURI JURNALI, 2025)
This article examines the formation of the ancient channels of the Amu Darya — the Okchadarya and Sarikamish channels — and their role in the geopolitical and economic development of the Khorezm oasis. It highlights the changes in the river’s flow, ancient irrigation systems, the settlement patterns of primitive societies, and the agricultural culture during the Neolithic and Classical periods. The article also presents scientifically grounded information on the Amu Darya’s connection to the Caspian Sea through the Uzboy, the processes of desertification in the region, and ancient transportation routes.